The Use of Role-Play Methods to Improve Assertiveness Skills in Early Childhood Education at Al-Hidayah Kindergarten - Nurul Hidayah; Pascalian Hadi Pradana; Ahmad Afandi (SAINTIS Publishing, 2025)
The purpose of this study is to improve the assertiveness skills of early childhood children through the application of role-playing methods in the Al-Hidayah Playgroup (KB). Through role-playing activities designed with themes close to the children's experiences, it is hoped that children can be more confident in communicating and demonstrating assertive behavior appropriate to their developmental stages. The research method used in this study is Classroom Action Research (CAR). This research was conducted in two cycles, where each cycle consists of four stages, namely planning, acting, observing, and reflecting. Based on the results of the research in the two learning cycles, there was a significant increase in the development of children's assertiveness skills in KB Al-Hidayah. In the first cycle, although the role-playing activity with the theme